2023
DOI: 10.32604/jrm.2023.026549
|View full text |Cite
|
Sign up to set email alerts
|

Materials Selection of Thermoplastic Matrices of Natural Fibre Composites for Cyclist Helmet Using an Integration of DMAIC Approach in Six Sigma Method Together with Grey Relational Analysis Approach

Abstract: Natural fibre reinforced polymer composite (NFRPC) materials are gaining popularity in the modern world due to their eco-friendliness, lightweight nature, life-cycle superiority, biodegradability, low cost, and noble mechanical properties. Due to the wide variety of materials available that have comparable attributes and satisfy the requirements of the product design specification, material selection has become a crucial component of design for engineers. This paper discusses the study's findings in choosing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Overall concept design attributes of pineapple polymer composite cyclist helmet liner (Leng et al, 2022;Maidin et al, 2023;Maidin et al, 2022;Kassar et al, 2016;Geum et al, 2011;Jayakrishna & Vinodh, 2017;Bhudolia et al, 2021;Novak et al, 2019) Parameter The design for concept 1 used less material and was thus considered less expensive than the others that used more material, such as designs for concepts 2, 3, and 4. However, concept 2 was the easiest to draw and design during the design stage, followed by concepts 3 and 4, whereas concept 1 was the most difficult to create due to the complicated elements.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Overall concept design attributes of pineapple polymer composite cyclist helmet liner (Leng et al, 2022;Maidin et al, 2023;Maidin et al, 2022;Kassar et al, 2016;Geum et al, 2011;Jayakrishna & Vinodh, 2017;Bhudolia et al, 2021;Novak et al, 2019) Parameter The design for concept 1 used less material and was thus considered less expensive than the others that used more material, such as designs for concepts 2, 3, and 4. However, concept 2 was the easiest to draw and design during the design stage, followed by concepts 3 and 4, whereas concept 1 was the most difficult to create due to the complicated elements.…”
Section: Tablementioning
confidence: 99%
“…The previous study by the same researchers showed that the pineapple/polyethene composite was the best natural fibre polymer-reinforced composite, with the natural fibre cycling helmet receiving the top ranking, according to the results. This study suggested thermoplastic polyethene as a particularly ideal matrix in composite cyclist helmets during the selection process for the best thermoplastic matrix material using the 6σ technique, with the decision based on the highest performance, the lightest weight, and the most environmentally friendly criteria (Maidin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Maidin et al 66 developed a systematic evaluation framework using GRA to rank natural fiber materials as reinforcement composites for cyclist helmets, with pineapple identified as the most suitable candidate for optimal safety. In another study, Maidin et al 67 applied 6 Sigma and GRA methods to select the most suitable thermoplastic matrix for natural fiber composites in cyclist helmets, integrating qualitative and quantitative approaches to identify thermoplastic polyethylene as the ideal matrix.…”
Section: Literature Reviewmentioning
confidence: 99%